An evaluation of the implementation of Curriculum 2013 at the building construction department of vocational high schoos in Yogyakarta - Amat Jaedun; V. Lilik Haryanto; Nuryadin Eko Rahardjo (LPPM UNY, 2014)
This research aims to determine the readiness of the teachers of the building construction department of vocational high schools (SMK) in Yogyakarta in designing and implementing the teaching and assessment processes of Curriculum 2013 implementation.The population was the teachers of building construction departments of the SMK’s in Yogyakarta, which had been selected as the pilots of Curriculum 2013 implementation in the academic year 2013/2014, namely: SMKN 2 Yogyakarta, SMKN 3 Yogyakarta, SMKN 2 Depok, SMKN 1 Seyegan, SMKN 2 Pengasih, and SMKN 2 Wonosari. A sample of 13 teachers was established using the quota sampling technique (three teachers for each package of specialization). The data were collected using a questionnaire and through documentation. The data were analyzed using the descriptive statistical, quantitative and qualitative descriptive analyses. The results of this research are as follows. (1) The teachers’ readiness in lesson planning to implement Curriculum 2013 measured from the availability of the learning tools, and the teachers’ ability to plan the learning processes, is in the less ready category. (2) The teachers’ readiness in implementing the learning process to implement Curriculum 2013 is in the less prepared conditions. The findings show that: (a) the teachers do not understand the principles and application of the scientific learning models as an appropriate approach to Curriculum 2013 implementation; (b) though all teachers have formulated learning activities preliminarily, the core and ending of learning stages, the realization of these activities is not in accordance with the provisions, (c) the teachers do not apply the information and communication technology (ICT) in the learning activities. (3) The teachers’ readiness in the learning assessment to implement Curriculum 2013 is in less prepared conditions. This is shown by the teachers’ inadequate understanding of the principles, procedures, and techniques of the authentic assessment, and the given tasks for the students do not portray the authentic tasks